حضـــــور التصـــــوف في أدب الرسائـــل رسائل الشيخ أحمد التّجاني أنموذجا - حميد، احلام, تواتي، نجاح (جامعة الوادي University of Eloued, 2019)
جاء التصوف الإسلامي مقترنًا بفكرة الزهد الذي أنتجه المتصوفة بمختلف اتجاهاته, ، فهو يبحث في النفس الإنسانية بعمق فلسفي يسعي لتطهير النفس والروح من حب الدنيا وزينتها، وإدخال الطمأنينة إليها. و يعتبر موضوع التصوف و علاقته بالطرق الصوفية و خاصة الطريقة التجانية من بين المواضيع التي أخذت جانبا مهما في هذا المجال, و لقد عبّرت هذه الطرق الصوفية عن مضامين منهجها الصوفي و ثمارها بطرق شتّى, لذا ارتأينا من هذا الباب أن نتناول موضوع بحثنا و المتمثل في:" حضور التصوف في أدب الرسائل, رسائل الشيخ أحمد التجّاني أنموذجا". و إن أبرز ما خلصنا له أنّ الشيخ أحمد التجّاني كان مقلدًا سلفه الصوفية في كل رسائله, فالمضامين نفسها التي جاء بها القشيري و ابن عربي و الحلاج و غيرهم, و قد كان أقرب للصوفية الأوائل منه للمتصوفة الفلاسفة Islamic mysticism came in conjunction with the idea of asceticism produced by the Sufis in all its directions. He is looking at the human soul with a philosophical depth that seeks to purify the soul and spirit from the love and adornment of the world and to bring reassurance to it. The subject of Sufism and its relation to mystical methods, especially the method of Tajanip among the topics that took an important aspect in this area, and these Sufi methods have expressed the contents of the Sufi approach and its fruits in various ways, so we have seen from this section to address the subject of our research, : "The presence of Sufism in the literature of messages, the messages of Sheikh Ahmed Tijani model." And the most prominent conclusion that Sheikh Ahmed Al-Tijani was imitating his Sufi predecessor in all his messages, the same contentions that came by the Quraysh and Ibn Arabi and Hallaj and others, and was closer to the mystics first of the mystics philosophers.
Keywords: التصوف ومضامينه في الرسائل; Sufism and its implications in letters